Management and reclamation of salt-affected soils: general assessment and experiences in the Brazilian semiarid region - Raj Gheyi, Hans (Revista Ciência Agronômica, 2021)
Salt-affected soils occupy extensive areas in arid and semi-arid regions around the world, and impact food production,particularly when salinization processes occur in irrigated areas. In this context, the possibility of using techniques for the reclamationof these soils needs to be considered. However, many of these techniques are inaccessible to most farmers in the Brazilian semi-aridregion, given the high costs, mainly when it is necessary to install a subsurface drainage system. Thus, there is a need to evaluate othersoil reclamation strategies as well as the possibility of using these areas for other purposes. This review covers topics related to thecharacterization and impacts of salt-affected soils, the infl uence of soil microorganisms, and strategies for soil reclamation, such as theuse of chemical and organic conditioners, bio-drainage, phytoremediation, and revegetation with tolerant species. The topics addressedin this review indicate new possibilities for the reclamation and management of salt-affected soils in the Brazilian semi-arid region. Acase study is also presented, which demonstrates that the use of salt-affected soils is defi ned by technical, social, and economic aspects.